Pengaruh Balance and Strength Tele-Exercise (BAST) Terhadap Kekuatan Otot dan Mobilitas Fungsional Lansia - Fadhia Adliah; Ita Rini; Widiarty Sulistyana Natsir; Tirta Sari (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2023)
Introduction; The musculoskeletal system, which greatly affects the balance of the elderly body and can cause mobility disorders, is one of the declines experienced by the elderly. Physical exercise in the form of muscle strengthening and balance exercises is an effective way for the elderly to improve their functional abilities. Purpose; This study is to determine how providing Balance and Strength Tele-Exercie (BAST) affects changes in lower extremity muscle strength and functional mobility in the elderly. Method; This is an experimental study with a one-group pretest-posttest design method. A total of 15 people aged 60-75 were analyzed using a purposive sampling technique. The 30s Chairs Stand Test, Functional Reach Test, and Time Up and Test were used to retrieve research data. Result; A significant value was obtained based on the bivariate analysis results. The muscle strength variable has a sign value of 0.005, the dynamic balance variable has a sign value of 0.003, and the functional mobility variable has a value of 0.001. Conclusion: This BAST program improves leg muscle strength and functional mobility in the elderly